(untitled) (Phenomenology, Humanities and Sciences, 2025)
The research aims to reflect on the question of the body and language, highlighting the lively interaction between these two poles in Merleau-Ponty’s thought. It will take into account the fact that the intrigue between the writings around the Phenomenology of Perception (1945) and those around the indirect ontology of Vertical Being addressed in The Visible and the Invisible (1961) and the Unpublished Writings (2013s), proves to be deeply instigating for an inexhaustible and renewed inquiry into the theme of the body and language from a genuinely embodied philosophy. In this context, the category of expression is a watershed in the philosopher’s thinking. It calls into question any misconception of associating the body and language with the idea of mere representation. After presenting the fundamental terms surrounding the category of body-self, which is inseparable from the authentic carnal existence of speaking subjects, we will try to highlight the way in which the philosopher challenges the limits of ordinary language in favor of the unprecedented diacritical character of language, which henceforth allows him to link indirect language to literary language and these to the new way of doing philosophy in contemporary times.